Gambaran Pelayanan Informasi Obat Terhadap Pasien Oleh Petugas Farmasi di Apotek X Kuningan - Chindi Suci Anggraeni; R Yulia Rochmawati (Jurnal Farmaku (Farmasi Muhammadiyah Kuningan), 2018)
This research was conducted with the aim to know the description of drug information services to patients by pharmacy officer in one of Apotek in Kuningan. The research design used is descriptive research, with sampling in this research is done with Purposive Sampling technique as many as 87 patients. Data obtained by filling the questionnaire consisting of 9 question items. Technical analysis of data used is using the formula percentage. From the results of data collection, it can be concluded that the level of knowledge of the patients on the understanding of drug use is categorized well with the average percentage result before the drug information service 78,13%, and after drug information service 85,94%.